Reclaiming the city: housing for inner-city Johannesburg - Harrison, Marianna (My University, 2009)
The way in which a city is spatially laid out effects the natural environment of the planet (for example: pollution and the depletion of natural resources) as well as the social environment (the community and daily life) of its residents. Through the exploration of various modern urban planning theories, I will begin to look at some different approaches to urban planning. This document favours the compact city approach which advocates higher densities, mixed use development, public transport and community living. This approach relates to initiatives currently underway in the inner city of Johannesburg. This document is about the exploration of how people live in the city and the issues surrounding housing in the urban context. The proposed architectural project is a housing scheme located in Newtown, Johannesburg. Central concepts include: urban regeneration, inner city living, visual variety in the urban realm, street edge conditions and public to private hierarchies
Keywords: Urban regeneration; Inner city living; Housing; Johannesburg